Association Between Patent Foramen Ovale and Overt Ischemic Stroke in Children With Sickle Cell Disease - Galadanci, Najibah A.; Johnson, Walter; Carson, April; Hellemann, Gerhard; Howard, Virginia; Kanter, Julie (Frontiers in Neurology, 2021)
Ischemic stroke is one of the most devastating complications of sickle cell anemia (SCA). Previous studies have shown that intracardiac shunting including patent foramen ovale (PFO) can be a potential risk factor for stroke in children with SCA. This study investigates the association between PFO and overt ischemic stroke in the DISPLACE (Dissemination and Implementation of Stroke Prevention Looking at the Care Environment) study cohort of 5,247 children with SCA of whom 1414 had at least one echocardiogram. Further, we assessed the association between PFO and other clinical and hemolytic factors in children with SCA such as history of abnormal sickle stroke screen (elevated Transcranial doppler ultrasound (TCD) velocity) and patient’s baseline hemoglobin. In this cohort, there is no evidence that the odds of having an overt ischemic stroke was higher among those with PFO compared to those without (OR: 1.49, 95% CI: 0.20- 11.03, p = 0.6994). Similarly, no evidence that the odds of having abnormal TCD is higher among those with PFO compared to those without (OR: 0.85, 95% CI: 0.17- 4.25, p = 0.8463). Overall, results showed much lower prevalence of PFO among children with SCA than previously published. We found no increased risk of stroke or abnormal TCD among those with PFO compared to those without PFO in children with SCD.